The Influence of Education, Minimum Wage and Human Development Index on Poverty in North Sumatra Province from 2015 to 2024 - Aprianto Situmorang; Annisa Ilmi Faried; Suhendi Suhendi (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of education, minimum wage, and the Human Development Index (HDI) on poverty levels across 33 regencies/cities in North Sumatra Province for the 2015-2024 period. Employing a quantitative approach with panel data regression analysis, this research establishes the Fixed Effect Model (FEM) as the optimal estimation model through a series of rigorous tests. The results indicate that, simultaneously, education, minimum wage, and HDI have a significant impact on poverty, with an explanatory power of 87.15%. Partially, all three variables exert a significant negative influence, indicating that enhancing human capital quality and wage standards effectively reduces poverty rates. The policy implications of these findings emphasize the importance of an integrated poverty reduction strategy through improved educational access, wage policies that ensure purchasing power, and the strengthening of health and living standard dimensions. Local governments should prioritize budget allocation to the sectors constituting the HDI to accelerate equitable poverty reduction throughout North Sumatra